1984
DOI: 10.1136/gut.25.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriuria and primary biliary cirrhosis.

Abstract: Patients with primary biliary cirrhosis have marked disturbances of humoral and cellular immunity, but an increased susceptibility to infection has not been described previously. We have observed, however, that patients with primary biliary cirrhosis have a high incidence of bacteriuria. This increased susceptibility to urinary infection has been studied and our findings are repoated. Methods PATIENTSPatients with primary biliary cirrhosis were diagnosed by the usual criteria,1 and classified into prefibrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(132 citation statements)
references
References 16 publications
3
124
0
5
Order By: Relevance
“…Two previous case-control studies came to differing conclusions about the link between PBC and the prevalence of bacteruria as verified by a urine test 9,16 : it was suggested that the lack of matching for age distribution, other risk factors for UTI like cirrhosis, and technical problems may have explained this. We investigated whether subjects remembered ever having, or being treated for UTI, and our results did not show a strong association between past UTI and PBC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two previous case-control studies came to differing conclusions about the link between PBC and the prevalence of bacteruria as verified by a urine test 9,16 : it was suggested that the lack of matching for age distribution, other risk factors for UTI like cirrhosis, and technical problems may have explained this. We investigated whether subjects remembered ever having, or being treated for UTI, and our results did not show a strong association between past UTI and PBC.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these used healthy age-matched controls 10 comparing 87 PBC cases with controls (healthy hospital staff and patients with liver disease) to study the frequency of D&C and hysterectomy. Two studies compared UTIs in 89 cases 9 and 160 cases 16 of PBC with unmatched controls with other liver diseases. The final study examined miscarriage in 38 cases using hospital inpatients as controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary tract infections have been reported by several authors to be more frequent in patients with PBC than in controls, with Escherichia coli being the main etiological agent. [36][37][38] More recently, our 2005 epidemiological study on 1032 patients with PBC and 1041 rigorously matched controls 9 confirmed the association of an increased risk of PBC not only with urinary tract infections but also with vaginal infections, lifestyle factors such as smoking, and previous pregnancies. We also showed that frequent use of nail polish was associated with a slightly increased risk of having PBC.…”
Section: Environmental Factorsmentioning
confidence: 79%